Методика вибору схем руху екскаваторів при влаштуванні котлованів - Коцій, Я. Й.; Kotsiy, Y. Y. (Видавництво Львівської політехніки, 2019)
Наведено методику вибору схем руху екскаваторів, пов’язану з перевіркою існуючих. Основою чинних методик є вибір схеми руху лобовою або бічною проходкою залежно від ширини котловану або траншеї і радіуса копання. Запропоновано аналітичну перевірку оптимальних варіантів із врахуванням підвищення ефективності роботи екскаваторів і мінімального часу на їх пересування. Оптимізація технологічних параметрів роботи екскаваторів при влаштуванні котлованів полягає в підвищенні продуктивності та ефективності їхньої роботи. Наведена у статті методика вибору схем руху екскаваторів, обладнаних зворотною лопатою, передбачає певні критерії вибору типорозмірів машин, зокрема: а) продуктивність машин, а також відповідність технічним впливам характеристик машин і геометричних параметрів виїмок; б) експлуатаційна змінна продуктивність екскаватора на об’єкті та продуктивність їх розробки; в) математичне очікування обсягу робіт на об’єкті; г) надійність машин; д) енергетичний показник комплексу машин; е) енерго-технологічні критерії моделей систем машин. У результаті є необхідність реально оцінити критерій вибору схем руху машин при влаштуванні виїмок. Встановлено взаємозв’язок продуктивності гідравлічних екскаваторів та геометричних параметрів котлованів. Уточнено області застосування різних схем роботи екскаваторів при влаштування котлованів різної конфігурації. Встановлено на основі аналітичних розрахунків оптимальні залежності при виборі схем руху екскаваторів.

The adduce technique of the moving schemes of excavators is connected with the checking of existing ones. The basis of the techniques is the choice of the flow pattern with the frontal or lateral drain depending on the width of the pit or trench and this basis can be named as a radius of digging. In this article an analytical check of the optimal variants is taken into account for increasing the efficiency of the work of excavators and the minimum time for their movement. Optimization of technological parameters of the work of excavators in the installation of pits is the increasing of their productivity and efficiency. In this article is given the method of selecting the schemes of movement of excavators which are equipped with a return shovel. It includes certain criteria for choosing the standard sizes of machines, which can be attributed to: а) productivity of machines and also conformity to technical influences of characteristics of machines and geometric parameters of the excavations; b) the operational variable of the excavators performance on the object and the productivity of their development; c) by the criterion of mathematical expectation of the volume of work on the object; d) by the reliability of machines; e) by the energy index of the complex of cars; f) according to the energy-technological criteria of models of the machine systems. As a result, there is a require for a realistic assessment of the criteria for selecting the schemes of movement of the machines at the site of the excavations. The article establishes the interconnection of the productivity of hydraulic excavators with the geometric parameters of the pits. Specified areas of application of different schemes of work of excavators in the arrangement of pits of different configurations. The arangement on the basis of analytical calculations of optimal dependencies in the choice of schemes of motion of excavators.
Method of selection of the scheme of movements of excavator's at arangement a pit
Keywords: схеми роботи екскаваторів; час на робоче пересування; продуктивність та ефективність екскаваторів; schemes of the work of excavators; time on working shift; productivity and efficiency of excavators; 691.535